Torpedo Expert System
Designed to simplify and expedite the learning process, Torpedo provides a list of skills for the swim, start, turn, and finish of all four competitive strokes at five levels of proficiency. Coaches can track swimmers' progress in mastering skills, graphically display the progress on the computer, and print reports listing the mastered skills and the information critical to learning the remaining skills.